What’s new in the etiotropic therapy of coronavirus infection? - A. V. Budnevsky (Лечащий Врач, 2022)
The increase in the number of cases of COVID-19 poses new challenges for Russian medical science to develop new drugs to combat this infection. After all, we are talking not only about the disease itself, but also about its consequences for the entire in the human body. Honored Inventor of the Russian Federation Andrey Budnevsky, Doctor of Medical Sciences, Professor, Head of the Department of Faculty Therapy of the Federal State Budgetary Educational Institution named after N. N. Burdenko, told us about the importance of the timely start of treatment, about new regimens for treating COVID-19 and about drugs developed by Russian scientists.